The Application of Nanotechnology and Nanomaterials in Depression: An Updated Review - Khushbu Yadav; Anjna Rani; Pankaj Tyagi; Malakapogu Ravindra Babu (Precision Nanomedicine, 2023)
Depression is the most common stress-related mental illness. It has an impact on millions of individuals globally. Genetic, biochemical, environmental, and psychological elements can all play a role in its development. Medications, psychotherapy, and lifestyle changes are frequently used to treat depression. Antidepressant medications work by altering the levels of certain chem-icals in the brain. At the same time, psychotherapy aims to help individuals better understand and manage their emotions and thoughts, which otherwise may lead to depression. The current treatment strategy for the illness has several drawbacks, such as adverse effects, ineffectiveness, long-term use, stigma, and cost-related issues of the medication used. These negative effects un-derscore the need for more successful and novel methods of treating depression, such as the investigation of medication delivery techniques based on nanotechnology. Increased medication effectiveness, fewer side effects, long-lasting medication effects, a good understanding of the neural underpinnings of depression, and the potential for the creation of personalized medicines are some of the potential benefits of using nanotechnology in depressive disorder treatment. In several scientific domains, nanotechnology has many benefits. Nanoparticles are the fundamen-tal building blocks of nanotechnology in this regard. Nanoparticles hold great promise for use in medical applications, as recently developed nanotechnology has shown. This review focuses on the most popular nanomaterials that are used to treat depression, in addition to how well these nanomaterials are at managing depression based on their physical, chemical, and biological properties. We have also talked about the difficulties that the various nanomaterials face, which limit their uses and prevent the development of effective clinical therapies.